KAPASITAS AEROBIK MAKSIMAL ATLET PENCAK SILAT PERGURUAN PAGAR NUSA - Saprian, Saprian; Purnomo, Edi; Hidasari, Fitriana Puspa (Universitas Tanjungpura, 2023)
Aerobic capacity is a problem that is often faced by sports athletes, especially pencak silat, many athletes often experience rapid fatigue in competing. This results in decreased concentration of athletes in competing and it is difficult to receive input from coaches for athletes who experience fatigue. So this is the background of the author to examine this problem. This study aims to measure the maximum aerobic capacity of pencak silat fence athletes. The method used in this research is a descriptive survey. The population in this study were pencak silat athletes from fence Nusa, and the research sample consisted of 20 people with different fighting classes. The instrument used in this research is the Bleep Test research technique (run back and forth). By using a voice recording that reads